Effectiveness of 6 weeks vestibular exercises practice on depression, anxiety, stress, and memory in hypertensive working women - Paramasivam Velu,; Bhanu Prakash Gangupalli,; Neelkanth Kote,; Sai Sailesh Kumar Goothy,; Joseph Kurien Mukkadan, (Asian Journal of Medical Sciences, 2022)
Background: There is a raise in the psychological problems globally. Depression, anxiety, and stress are the negative psychological emotions that have to be diagnosed and managed at earlier stages. Vestibular stimulation was known to manage the negative psychological emotions. Aims and Objectives: The aim of the study was to observe the effectiveness of selective vestibular exercises on depression, anxiety, stress, and memory in hypertensive working women. Materials and Methods: A total of 20 working women with untreated pre-hypertension to Stage I hypertension and 20 healthy age-matched controls (working women), after obtaining written and informed consent. Results: There was a significant improvement in the depression, anxiety, and stress scores followed by the practice of vestibular exercise. Spatial memory was significantly improved followed by practice of vestibular exercise for 6 weeks. Although there was an improvement in the verbal memory, but it was not statistically significant. Conclusion: The study results present significant improvement in the depression, anxiety, and stress scores and significant improvement in spatial memory followed by the vestibular exercises for 6 weeks. The study recommends further detailed study with higher sample size to recommend vestibular exercise in the management of negative emotions and to improve memory.